Rancang Bangun Aplikasi Mobile Foodaround dengan Augmented Reality untuk Memperkenalkan Makanan Tradisional Betawi - Pangestu, Timothy Daniel; Barus, Simon Prananta (Jurnal Informatika Terpadu, 2024)
Indonesia has a rich culinary cultural heritage, including traditional Betawi cuisine. However, this culinary heritage is increasingly being eroded among the younger generation. This research aims to develop a mobile application named FoodARound that uses markerless Augmented Reality (AR) technology to introduce traditional Betawi food to a broader audience. The application visualizes 3D objects of foods such as kerak telor, kue cucur, and selendang mayang, and provides information on the ingredients and how to make them. A prototyping method was used in the development of the application, including needs analysis, prototype creation, prototype evaluation, and implementation. Unity and Vuforia were used as the AR application development platforms, while Firebase Realtime Database was integrated to store food data. Black box testing was conducted to validate the functionality of the application. The research results show that the FoodARound application was successfully developed and can be used as an interactive medium to introduce traditional Betawi food to the public, especially the younger generation. AR technology provides an engaging experience for learning about local culinary heritage. This research highlights the importance of technological innovation in preserving culture and traditional culinary education.